Peningkatan Ketrampilan UKM Logam Melalui Pelatihan Pembuatan Mesin Perajang Bawang Merah Di Kota Nganjuk - Santoso, Eko Budi; ., Saat Riyanto; Herraprastanti, Eva Hertnacahyani; ., Ichlas Imran; ., Windarti . (Vokasi Universitas Halu Oleo, 2020)
Nganjuk is one of the agrarian cities in East Java that has great potential in producing shallots. Shallots sold are in the form of leafy or leafless onions which are usually called